The Influence Of Entrepreneurship Marketing Systems And Innovation On Competitive Advantage On Culinary Of UMKM In Bandung City - Dwiki Kurniawan, Muhammad Fariz; Dzulfikar, Muhamad Fajar; Ramadhan, Fakhri; Wijaya, Tomi Ikbal; Feronika, Yohana (Jurnal Manajemen Industri dan Logistik, 2022)
The purpose of this study is to determine whether the marketing system of entrepreneurship and innovation has an effect on the competitive advantage in the food of UMKM in the City of Bandung. The population used in this study derived data from a questionnaire that is distributed to UMKM in the City of Bandung, with the last sample of 123 respondents using the method of test, the classical assumption that in the test with the tests of normality, test heteralitas, trial serentitas multisoility, and some analysis subefisensi by using deduction regression. The results of the analysis of the data of the state that entrepreneurship and marketing system innovation have a positive effect or significant in the variable competitive advantage, both of them are seen simultaneously